Effect of regular physical activities and daytime nap intervention on enhancing mental health and self-esteem in healthy participants - Mohammad Ahsan; Mohammed Feroz Ali; Abdullah Alzahrani; Abdullah Alhusayni; Mumtaz Alam (Journal of Education and Health Promotion)
BACKGROUND: Regular physical activity and proper rest play a significant role in the quality of life of every individual. The purpose of this study was to investigate the effect of physical activities and daytime naps on mental health and self-esteem. MATERIALS AND METHODS: A pretest and posttest study design was selected with 95 participants who were randomly assigned to two groups. Forty-five participants were part of the interventional group, whereas 50 participants were assigned to the control group. The interventional group participated in physical activities and took a short nap of less than 20 min per day three times a week for 12 weeks. Meanwhile, control group participants were free to do daily activities without participating in any sports activity. Participants’ mental health and self-esteem were measured before and after 12 weeks. Data were compared using the Wilcoxon signed-rank test and Mann–Whitney U test. RESULT: The results showed no significant difference between pre-and post-test in mental health (P = 0.072) and self-esteem (P = 0.061) for the control group, whereas the interventional group showed a significant difference between pre-and post-test for mental health (P ≤ 0.001) and self-esteem (P ≤ 0.001), and mean scores for mental health (59.16 ± 10.43) and self-esteem (25.62 ± 3.35) were higher than pretest (55.00 ± 11.68) (22.93 ± 1.80) scores. Mental health and self-esteem improved in the interventional group when compared with the control group after 12 weeks. CONCLUSION: The findings revealed that the interventional group had significantly higher mental health and self-esteem than the control group. Physical activities may improve mental health, self-esteem, and overall wellness. To obtain these benefits and preserve a quality of life, daily physical exercises and mandatory rest are necessary. Therefore, policymakers should prioritize these interventions to promote the overall health of such populations.